PENERAPAN PENDIDIKAN KARAKTER, PENDEKATAN SESOSIFIT (SPIRITUAL, EMOSIONAL, SOSIAL, INTELEKTUAL, FITRAH) MELALUI LAYANAN BIMBINGAN DAN KONSELING - Ahmad, Karyono Ibnu (Tarbiyah, 2014)
One of the causes of character education crisis on the children today is because almost all parents give the responsibility to educate their children completely to the schools.On the contrary, the schools are overburdened with the academic curriculum while in the society âjob creationâ (steady job) is more demanded. Thus, the charater education for the children is then abandoned. The character education can be implemented through SESOSIFIT approach (spiritual, emotional, social, intellectual, and fitrah). Parents, teachers/counselors, and community leaders should have to provide guidance and counseling services for the students by inserting the SESOSIFIT values as the moral-religious teaching. They should also have to motivate students by teaching them that any activities they do are part of the worship, and improve the quality of paith and peity. Besides, in providing guidance and counseling, problematic student/client can also solve his/her own problems based on the guidance from the holy Quran, and the prophet tradition with the guidance to find the clues him/herself.Keyword:spiritual, emotional, social, intellectual, fitrah, guidance and counseling